IMPLEMENTASI PEMBERDAYAAN PEREMPUAN MELALUI PROGRAM PENINGKATAN PERANAN WANITA MENUJU KELUARGA SEHAT SEJAHTERA DI KELURAHAN KEPUH - Utami, Rezza Widia; Afrizal, Stevany (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
efforts to empower women to gain access and control over resources, economy, politics, social, culture, so that women can self-regulate and increase self-confidence to be able to play a role and participate actively in solving problems, so as to be able to build abilities and self-concept, namely through empowering women. Empowerment needs to be realized in the form of empowerment programs that are able to empower all the potential that exists in the community through programs to increase the role of women towards healthy and prosperous families. The purpose of this study was to identify and describe the implementation of Women's Empowerment through the Program for Increasing the Role of Women Towards a Healthy and Prosperous Family (P2WKSS) in Cikendat Village, Kepuh Village, Ciwandan, Cilegon. This study uses descriptive qualitative research methods, in data collection is done by observation, interviews and documentation. The results showed that the implementation of women's empowerment in the P2WKSS program was through women's training. There are four trainings, namely beauty/makeup, cooking/cooking, handicrafts, and sewing. And increase women's participation and awareness in the P2WKSS Program and the impact of social changes felt due to the P2WKSS program. The benefits of implementing the P2WKSS Program are (1) Improving social conditions seen from the enthusiasm of women's participation. (2) increase women's awareness through four P2WKSS training programs (3) Increase women's independence.